2018
DOI: 10.1042/bsr20180636
|View full text |Cite
|
Sign up to set email alerts
|

Fate of uptaken host proteins in Taenia solium and Taenia crassiceps cysticerci

Abstract: During the study of host-parasite relationships in taeniid parasite diseases, including cysticercosis and hydatidosis, reports have described the presence of host proteins in the cyst fluid and tissue of metacestodes. However, the fate or role of host elements inside the parasite remains barely explored. After the publication of genomes of four cestode species, it became clear that these organisms possess a limited biosynthetic capability. The initial goal of the present study was to determine if uptaken host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In our experiments, C57BL/6 mice were easily infected and mounted a significant humeral response to the parasite, as evidenced by the presence of T. crassiceps targeting antibodies in the serum. In addition, we were able to corroborate recent research, which has shown that the larvae themselves can take-up and release host protein, including IgG (Flores-Bautista et al, 2018). We found that even after 10 days in culture T. crassiceps larvae were still releasing host IgG and cytokines into the culture media.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our experiments, C57BL/6 mice were easily infected and mounted a significant humeral response to the parasite, as evidenced by the presence of T. crassiceps targeting antibodies in the serum. In addition, we were able to corroborate recent research, which has shown that the larvae themselves can take-up and release host protein, including IgG (Flores-Bautista et al, 2018). We found that even after 10 days in culture T. crassiceps larvae were still releasing host IgG and cytokines into the culture media.…”
Section: Discussionsupporting
confidence: 86%
“…To modulate the host immune response, Taenia larvae produce and excrete/secrete molecules which impair dendritic cell maturation and promote Th2-driving ability (Terrazas et al, 2010). Furthermore, the larvae can sequester and dispose of host immune proteins, including IgG (Flores-Bautista et al, 2018). The effect of these systemic parasite-induced host immune responses on the brain is still relatively uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most abundant host proteins reported are serum albumin and immunoglobulins [ 87 , 190 ]. In the case of the former, the parasite can use it to maintain internal osmotic pressure, whereas the latter could help to prevent antigen exposure of the immune system [ 192 , 193 ]. Surprisingly, it has been reported that these organisms can incorporate various host antioxidant proteins to their antioxidant repertoire, such as the SOD, Prxs, and CAT isoforms [ 81 , 87 ].…”
Section: Adaptations Of Parasitic Flatworms To Changes In Oxygen Tensionmentioning
confidence: 99%
“…The cysticerci can utilize several mechanisms to evade or downregulate both the humoral and cellular arms of the host immune response ( 180 ). Modulation of the humoral immune response occurs in several ways including by taking up host immunoglobulins (IgG, IgM, IgE and IgG) in the cyst tegument to mask parasite antigens ( 196 ) and by releasing molecules (such as taeniastatin), which inhibit the complement pathway ( 197 ). Taenia cysticerci also modulate cells of the immune system in multiple ways.…”
Section: Neurocysticercosis In Africamentioning
confidence: 99%